On the prime spectrum of top modules - Ansari-Toroghy, H.; Hassanzadeh-Lelekaami, D. (Algebra and Discrete Mathematics, 2011)
In this paper we investigate some properties of top modules and consider some conditions under which the spectrum of a top module is a spectral space.